The early assessment of harmful algal bloom risk in the East China Sea. (May 2022) - Ding, Wenxiang; Zhang, Caiyun; Shang, Shaoping
Abstract: The East China Sea (ECS) is seriously impacted by harmful algal blooms (HABs). Therefore, early assessments of HAB risk in this area are extremely important. Using long-term historical HAB observation data and satellite-derived sea surface temperatures (SSTs), we found that the annual number of HAB events was positively correlated with the mean March SST and negatively correlated with the SST change rate from March to July in nearshore waters (< 50 m). A simple method of HAB risk assessment was therefore proposed based on either March SST (threshold: 13 °C) or SST change rate (threshold: 3.6 °C/month). Validation against a k-means classification scheme indicated that the overall accuracy based on the March SST threshold was 85%, with a kappa coefficient of 0.69. The SST-based method facilitates the assessment of HAB risk in the ECS 1–2 months in advance, thus helping to reduce the damage caused by HABs. Highlights: A simple method for the early assessment of HAB risk is proposed based on March SST (13°C) and SST change rates (3.6°C/month) thresholds. HAB frequency was positively and negatively correlated with March SST and SST change rate, respectively. The overall classification accuracy using the March SST threshold was 85%, with a kappa coefficient of 0.69.